Analysis of the effect of turbulence promoters in hollow fiber membrane distillation modules by computational fluid dynamic (CFD) simulations - Yang, Xing (2013)
As an extended exploration of process enhancing strategies, nine modiﬁed hollow ﬁber modules with various turbulence promoters were designed and modeled using a two dimensional computational ﬂuid dynamic (CFD) heat-transfer model to investigate their potential in improving heat transfer and module performance for a shell-side feed direct contact membrane distillation (DCMD) system. With the aids of turbulence promoters, the feed heat-transfer coefﬁcient hf of the modiﬁed modules generally showed much slower decreasing trends along the ﬁber length compared to the original (unmodiﬁed) module. A 6-fold hf enhancement could be achieved by a modiﬁed module with annular bafﬂes and ﬂoating round spacers. Consistently, the temperature polarization coefﬁcient (TPC) and mass ﬂux distribution curves of these modiﬁed modules presented increasing trends and gained an optimal improvement of 57% and 74%, respectively. With the local ﬂow ﬁelds and temperature proﬁles visualized in CFD simulations, it was conﬁrmed that an appropriate selection of turbulence promoters could promote intense secondary ﬂows and radial mixing to improve the shell-side hydrodynamics and enhance heat transfer. Moreover, an increase of ﬂow velocity was used and compared as a conventional approach to improve hydrodynamics. It was found that a well-designed module could bring more signiﬁcant enhancement for a liquid-boundary layer dominant heat-transfer process. Finally, the hydraulic energy consumption (HEC) caused by the insertion of turbulence promoters or the increase of circulating velocity was compared. Conﬁgurations with attached quad spacers or ﬂoating round spacers achieved a good compromise between enhanced permeation ﬂuxes and modest HECs. Overall, the TPC decreases with increasing MD coefﬁcient (C) values and operating temperatures; while the thermal efﬁciency increases dramatically with increasing C and operating temperatures in a MD system.